Kontribusi Pemikiran Hasbi Ash-Shiddieqy dalam Kajian Ilmu Hadis - Supian, Aan (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2014)
The studies of hadith and scientific reseaches in Indonesia found the momentum around the end of the 20th century. One of the figure whose enough concern on this field is Hasbie Ash-Shiddieqy. Some of Hasbie’s thoughts in the hadith field which is become point of view in this article include: First, his view on the substance of the hadith and Sunnah and its periodization. Secondly, the criteria of hadith’s validity. Third, the research and the maintenance of hadîth. Fourth, the methodology of understanding the hadith (sharh al-hadîth). Hasbi thought that the hadith are all events that leaning to the Prophet Muh}ammad, although it happened only once in the lifetime of the Prophet, and although only narrated by a narrator. Then Sunnah is the actions of the Prophet Muh}ammad that mutawâtir. Validity of hadith in Hasbi’s point of view must include of two criteria, that is the validity (sahîh) of sanad and matn of hadith. Hasbi seems to emphasize a study of the hadiths that the quality is not clearly by applying the criteria of validity of the hadith and the theory of nâsikh wa mansûkh